Fractal Image Coding with Digital Watermarks - Candik, M.; Levicky, D.; Klenovicova, Z. (Společnost pro radioelektronické inženýrství, 2000)
In this paper are presented some results of implementation of digital watermarking methods into image coding based on fractal principles. The paper focuses on two possible approaches of embedding digital watermarks into fractal code of images - embedding digital watermarks into parameters for position of similar blocks and coefficients of block similarity. Both algorithms were analyzed and verified on gray scale static images.
Keywords: fractal image coding; digital watermarking